A percepção dos servidores da UNIFAL-MG sobre o programa de avaliação de desempenho: uma análise empírica e um balanço perspectivo após dez anos. - Nilda Aparecida de Carvalho Gonçalves (Revista ft, 2026)
This article analyzes the perception of administrative staff (servidores técnico-administrativos em educação) and faculty holding leadership positions at the Federal University of Alfenas (UNIFAL-MG) regarding the Performance Evaluation Program. Supported by Law No. 11,091/2005, which established the Career Plan for Administrative Staff in Education (PCCTAE) within Federal Higher Education Institutions (IFES), the study investigates the extent to which the evaluation process fulfills its pedagogical and managerial functions. The research is based on a quantitative and descriptive approach, with data collection conducted through questionnaires administered to a non-probability convenience sample of 371 civil servants who participated in the 2016 evaluation cycle. The results indicate that, although most respondents recognize the importance of evaluation and self-evaluation for institutional and individual development, knowledge regarding the program’s objectives remains superficial. Furthermore, severe operational weaknesses were identified, notably the lack of prior training and the systematic absence of feedback. It is concluded that performance evaluation at UNIFAL-MG is perceived primarily as a bureaucratic rite aimed at granting career progression based on professional merit. In addition, the study offers a prospective analysis of the transformations that have occurred over the past decade, evaluating the impact of digital modernization, telework, and new competency-based management guidelines in the public sector.